2021
DOI: 10.1007/s11154-021-09695-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic signatures after bariatric surgery – a systematic review

Abstract: Metabolomics emerged as an important tool to gain insights on how the body responds to therapeutic interventions. Bariatric surgery is the most effective treatment for severe obesity and obesity-related co-morbidities. Our aim was to conduct a systematic review of the available data on metabolomics profiles that characterize patients submitted to different bariatric surgery procedures, which could be useful to predict clinical outcomes including weight loss and type 2 diabetes remission. For that, the Preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 94 publications
0
13
0
2
Order By: Relevance
“…Os procedimentos de tipo misto, combinam a redução física do volume do estômago com um bypass intestinal. (20) A cirurgia bariátrica deve ser considerada no algoritmo de tratamento do diabetes tipo 2 para todas as classes de obesidade.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os procedimentos de tipo misto, combinam a redução física do volume do estômago com um bypass intestinal. (20) A cirurgia bariátrica deve ser considerada no algoritmo de tratamento do diabetes tipo 2 para todas as classes de obesidade.…”
Section: Resultsunclassified
“…(17) Segundo Vaz, a cirurgia bariátrica é o tratamento mais eficaz para a obesidade grave e suas comorbidades associadas, uma vez que tem demonstrado alcançar com sucesso uma diminuição significativa e sustentada do índice de massa corporal, além de melhorar várias doenças relacionadas à obesidade, como diabetes tipo 2. (20) Atualmente, a maioria dos procedimentos bariátricos em todo o mundo são realizados por via laparoscópica porque a cirurgia minimamente invasiva está associada a menor tempo de internação, menores complicações gerais e menores custos em comparação com procedimentos abertos. (21) Analisando a tabela 1, se percebeu que os estudos apontam melhora dos níveis glicêmicos com a cirurgia bariátrica, assim como apontado por Chen X., Zhang J., Zhou Z., que dizem em seu…”
Section: Recima21 -Revistaunclassified
“…The effect is far from simply mechanistic and includes modulation of neural circuits, alterations of the intestinal microbiome, changes in bile acid excretion, restoration of the intestinal and adipose tissue hormonal milieu (with emphasis on the dynamic balance between incretins and anti-incretins, notably glucagon-like peptide-1 (GLP-1), peptide YY, leptin, ghrelin and glucose-dependent insulinotropic peptide), and recruitment of intestinal glucose transport molecules [ 7 ]. Among these mechanisms, the metabolome constitutes a relatively novel, upcoming and promising area of vigorous scientific research in the fields of bariatric and metabolic surgery, as it has been shown in three recent reviews [ 11 , 12 , 13 ].…”
Section: From Bariatric To Metabolic Surgery—a Name Change or A Game-...mentioning
confidence: 99%
“…With regard to BMS, the metabolome has been implicated both as a means to interpret the effects of BMS and as a scaffold of surrogate markers for predicting metabolic and bariatric outcomes on an individualized basis. Regarding the former area of interest, the trends of metabolites following BMS as documented in the literature are as follows— AA derivatives : decrease in BCAA (Leu, Ile, Val), AAA (Phe, Tyr, Trpؘ–kynurenine pathway), increase in serotonin, indoxysulfate, indole-3-propionic acid, glycine, and serine; lipid derivatives : decrease in free fatty acids (FFA), short-(C3, C5), medium-, and long-chain acylcarnitines, unsaturated and long-chain saturated fatty acids (LCSFA), triglycerides, ceramides, ketone bodies (late postoperatively), increase in medium-chain saturated fatty acids (MCSFA), decanoid acid, phosphatidylcholine, phosphatidylethanolamines, ketone bodies (early postoperatively); bile acids : increase in primary and secondary bile acids; microbiota-related metabolites : increase in trimethylamine-N-oxide, phenyl sulfate, p -cresol; TCA-related metabolites : decrease in pyruvate and lactate, increase in citrate, succinate, and malate; endocannabinoids : decrease in 2-arachidonoylglycerol, anandamide, arachidonic acid [ 13 , 14 ]. As far as prediction is concerned, relevant studies focus mainly on the relationship of various compounds with T2DM remission [ 12 , 15 , 16 , 17 , 18 , 19 ], and to a lesser extent, with (suboptimal) weight loss [ 20 , 21 ].…”
Section: The Metabolome As a Field Of Studying The Effects Of Bariatr...mentioning
confidence: 99%
See 1 more Smart Citation